2023
DOI: 10.3390/pharmaceutics15041131
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Peptide-Based Nano-Sized Cathepsin B Inhibitor for Anticancer Therapy

Abstract: Numerous cathepsin B inhibitors have been developed and are under investigation as potential cancer treatments. They have been evaluated for their ability to inhibit cathepsin B activity and reduce tumor growth. However, they have shown critical limitations, including low anticancer efficacy and high toxicity, due to their low selectivity and delivery problems. In this study, we developed a novel peptide and drug conjugate (PDC)-based cathepsin B inhibitor using cathepsin-B-specific peptide (RR) and bile acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Development of cathepsin B inhibitors: The development of cathepsin B inhibitors is an active area of research due to their potential as a therapeutic target for cancer and other diseases. Several studies have reported the development of small-molecule inhibitors of cathepsin B, including CA074, E6446, and CA045 [ 42 ]. However, none of these inhibitors have shown strong enough anticancer effects to be clinically available, and there are currently no FDA-approved cathepsin B inhibitors for cancer treatment [ 42 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Development of cathepsin B inhibitors: The development of cathepsin B inhibitors is an active area of research due to their potential as a therapeutic target for cancer and other diseases. Several studies have reported the development of small-molecule inhibitors of cathepsin B, including CA074, E6446, and CA045 [ 42 ]. However, none of these inhibitors have shown strong enough anticancer effects to be clinically available, and there are currently no FDA-approved cathepsin B inhibitors for cancer treatment [ 42 ].…”
Section: Reviewmentioning
confidence: 99%
“…Several studies have reported the development of small-molecule inhibitors of cathepsin B, including CA074, E6446, and CA045 [ 42 ]. However, none of these inhibitors have shown strong enough anticancer effects to be clinically available, and there are currently no FDA-approved cathepsin B inhibitors for cancer treatment [ 42 ]. Developing potent and selective low-molecular cathepsin B inhibitors relies on the detailed expertise of preferred amino acid and inhibitor residues [ 43 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, CtsB is the subject of numerous studies aimed at developing inhibitors to mitigate its activity in various conditions. The efficacy of CtsB inhibition has been tested in ameliorating a spinal cord injury by inhibiting macrophage ferroptosis [15] and treating cancer through the development of small molecules, such as the Nostoc-species-derived oxadiazine Nocuolin A [16], or biologics based on peptides [17,18]. The critical roles and regulatory pathways mediated by CtsB in various forms of regulated cell death, including pyroptosis, ferroptosis, necroptosis and apoptosis [19], make this enzyme highly attractive for developing new strategies based on inhibitory approaches.…”
Section: Introductionmentioning
confidence: 99%